FUNDAMENTAL ASPECTS OF THE 1988 CONSTITUTION - Ferreira Filho, Manoel Gonçalves (PANORAMA OF BRAZILIAN LAW)
This article is intended as an introduction, essentially informative in nature, to the Brazilian Constitution, which came into force on October 5, 1988.